(untitled) (Revista de História da UEG (REVHIST), 2025)
This article analyzes, using an ethnographic and qualitative anthropological approach, the dynamics, displacements and socio-spatial occupation of peripheral populations in central areas of Teresina (PI), and the dynamics of forced migration, cultural resistance and struggle for recognition, highlighting how urban fragmentation makes vulnerable groups invisible (Vidal, Musset and Vidal, 2011; Lima, 2023; Levy, 2001). The research confronts classical models such as Burgess’s (1921) and the center-periphery dichotomy (Velho, 1967), revealing that urban mobilities and dynamics reconfigure social structures and social practices. Teresina presents itself as a stage for tensions of vulnerability between spatial planning and appropriation, marked by social exclusion (Harvey, 2004) and the commodification of the city (Telles, 2015). Advocates the promotion of inclusive public policies that value peripheral identities and promote a cosmopolis with new policy practices. Keywords: Urban Anthropology. Center and Periphery. Teresina.